Building on Conceptual Interpretations of Aboriginal literacy in Anishinaabe Research: A Turtle Shaker Model - Debassige, Brent (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
This article comes out of the larger context of my dissertation research. <span lang="EN-US" style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi;">My dissertation is an investigation of my experiences as an academic who attempts to remain true to Indigenous Knowledge (IK) traditions while working within a Western European intellectual setting. <span lang="EN-US" style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In this article, I combine the conceptual frameworks of Aboriginal literacy and Cavanagh’s (2005) holistic educational model of the Anishinaabe teaching wand to create a holistic model of Anishinaabe literacy. I then present the ethical responsibility in protecting and sustaining Indigenous Knowledge. Finally, I share a personal narrative and detail a central model of Anishinaabe literacy from my dissertation—the (carving) of a turtle shaker<span lang="EN-US" style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">.